An Animation Video as a Distraction Strategy on Behavioral Response to Pain among Children Receiving Immunization- A Quantitative Study - Molly Saldhana; Malathi K; Sunanda Govinder Thimmajja (RGUHS Journal of Nursing Sciences)
Background Immunization provides protective immunity and immunological memory to individuals families and communities against any infectious diseases. As immunization is a painful procedure for children it may result in fear and anxiety regarding the procedure in the future. So itrsquos necessary to manage the pain by using different distraction strategies. So our aim was to assess the effectiveness of an animation video as a distraction strategy to reduce pain while immunization.Methods A quasi-experimental non-equivalent post-test only control group design was used to evaluate the usefulness of an animation video as a strategy of distraction to reduce pain while immunization among a sample of 60 children who were selected using a purposive sampling technique. An animated video was used as a distraction strategy to reduce the behavioral response to pain among children. Data was collected through demographic proforma and FLACC scale. Collected data were analyzed using descriptive and inferential statistics.Results The results demonstrated that the calculated mean difference between the control group and the experimental group was 4.56 and the lsquotrsquo test value was 8.59 which was greater than the table value at 0.05 level of significance indicating that animation video reduced pain among children in the experimental group. Thus the distraction strategy is helpful in reducing pain while immunization.Conclusion The findings of the study showed that there was difference in behavioral response to pain in control group and experimental group following distraction using animated video which inferred that the distraction strategy is helpful in reducing pain among children during immunization process.